2013
DOI: 10.1179/1743133613y.0000000066
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nickel on microstructure and wear behaviour of pure aluminium against steel and alumina counterfaces

Abstract: In this study, aluminium-nickel alloys with different Ni ratios ranging from 1 to 5 wt-% were produced by casting method. The effect of nickel on the microstructure and hardness properties was studied. The dry sliding wear response of the Al-xNi alloys against steel and alumina counterfaces was investigated. Worn surfaces of the alloys were examined using scanning electron microscopy. The results showed that the hardness of the alloys increases with increasing nickel content. Severe wear damage was observed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
1
7
0
1
Order By: Relevance
“…The wear resistance of the alloys increased with increasing nickel content up to 3 wt.% Ni and tended to decrease >3 wt.% Ni. The wear rate of the Al-xNi alloys increased with increasing applied normal load [51]. One of the disadvantages with Al is that it leads to corrosion.…”
Section: Wear Behaviour Of Aluminium-based Metal Matrix Compositesmentioning
confidence: 98%
See 2 more Smart Citations
“…The wear resistance of the alloys increased with increasing nickel content up to 3 wt.% Ni and tended to decrease >3 wt.% Ni. The wear rate of the Al-xNi alloys increased with increasing applied normal load [51]. One of the disadvantages with Al is that it leads to corrosion.…”
Section: Wear Behaviour Of Aluminium-based Metal Matrix Compositesmentioning
confidence: 98%
“…From the pin on disc wear tests performed under 67 N and with 1250 m sliding distance, it was revealed that the ultrasonic treated and non-treated samples exhibited similar amounts of weight loss [50]. Yamanoglu et al [51] studied the effect of nickel (1-5 wt.%) on microstructure and pin on disc wear behaviour of pure aluminium against steel and alumina counter faces. The dry sliding wear response of the Al-xNi alloys against steel and alumina counter faces was investigated [51].…”
Section: Wear Behaviour Of Aluminium-based Metal Matrix Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…The weight loss of specimens during wear tests was measured by weighing the specimens before and after the wear tests. The wear loss values obtained were used to calculate wear rate according to the following equation: W = M/ρD, where W is wear rate (cm 3 m -1 ), M denotes mass loss (g) and ρ (gcm -3 ) and D (m) are the density and sliding distance respectively [36]. The effect of titanium addition on the wear rate of the materials can be seen in Fig.…”
Section: Wear Testsmentioning
confidence: 99%
“…Bu nedenle W = M/D eşitliği kullanılarak ağırlık kaybı değerleri aşınma oranına dönüştürülmüştür. Bu formülde W aşınma oranını (mm 3 m -1 ), M ağırlık kaybını (g),  yoğunluk (gcm -3 ) ve D (m) sürtme mesafesini göstermektedir [18]. Titanyum ilavesinin malzemenin aşınma dayanımına etkisi Şekil 6'da gösterilmiştir.…”
Section: Aşınma Testleriunclassified